2021
DOI: 10.1007/s11033-021-06776-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and epidemiologic profiles of human metapneumovirus infection among children with severe acute respiratory infection in Huzhou, China

Abstract: Background Human metapneumovirus (hMPV) is one of the important pathogens in infant respiratory tract infection. However, the molecular epidemiology of hMPV among children < 14 years of age hospitalized with severe acute respiratory infection (SARI) is unclear. We investigated the hMPV infection status and genotypes of children hospitalized with SARI from January 2016 to December 2020 in Huzhou, China. Methods A nasopharyngeal flocked swab, nasal wash, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The detection rate of ADV in 2019 was extremely high all year round, peaking in summer. Infection caused by ADV can occur throughout the year; it mainly occurs in winter and spring in northern China, and is common in spring and summer in southern China ( Ji et al., 2021 ). In 2019, the detection rate of ADV was high all year round in Chongqing.…”
Section: Resultsmentioning
confidence: 99%
“…The detection rate of ADV in 2019 was extremely high all year round, peaking in summer. Infection caused by ADV can occur throughout the year; it mainly occurs in winter and spring in northern China, and is common in spring and summer in southern China ( Ji et al., 2021 ). In 2019, the detection rate of ADV was high all year round in Chongqing.…”
Section: Resultsmentioning
confidence: 99%
“…The highest coverage of the population with hRSv and hRv during the specified period was also recorded in other countries [ 46 – 48 ]. At the same time, several researchers have noticed the leading role of hMpv, hPiv as well as a significant contribution of hAdv in the general non-influenza viral pathology of the respiratory organs [ 35 – 37 , 49 , 50 ]. It is therefore possible to point out the territorial heterogeneity in the distribution of viral agents.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype Reference Sequence Selection: We performed an extensive literature review of articles describing HMPV molecular epidemiology and registered 327 HMPV sequences used as genotype references in 22 different articles; 19 of these articles focused on genotype assignment using the HMPV G gene. Subsequently, we selected sequences that have been used as genotype reference by several authors or sequences of newly identified genotypes for viruses with partial G gene duplications [ 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. As our aim focused on genotype assignment using the HMPV G gene ectodomain, sequences with at least the complete ectodomain were selected as references.…”
Section: Methodsmentioning
confidence: 99%